Design and Realization of Dual Band Microstrip Monopole Antenna - Mahouti, Peyman; Gunes, Filiz; Belen, Mehmet A.; Caliskan, Alper; Demirel, Salih (IEEE, 2016)
Herein, design and experimental results of a dual band Microstrip Monopole antenna are presented. The proposed antenna consists of a zig-zag microstrip line as monopole patch alongside of a Defected Ground structure under the fed-line of the antenna for size miniaturization propose, fabricated on FR4. The 10-dB bandwidth and gain performances are measured as 130 MHz and 6 dB at the centre frequency of 2.42 GHz, and140 MHz, and 2dB at the centre frequency of 5.92 GHz respectively.
Keywords: Microstrip; Monopole; ISM band; Miniaturized; Engineering; Telecommunications